Pengawasan Kelayakan Kapal Ikan oleh Kantor Kesyahbandaran Dan Otoritas Pelabuhan Kelas II Benoa - Prasetya, Dwita Erwin; Winaya, I Ketut; Dwi Wismayanti, Kadek Wiwin (CITIZEN CHARTER, 2020)
In the Minister of Transportation Regulation No.13/2012. The purpose of this study was to determine the supervision carried out by Benoa Class II Port Authority and Port Authority Office. The analysis of this research unit is to see the Supervision of the Feasibility of Fishing Vessels carried out by the Benoa Class II Port Authority and Port Authority Office. In this study, it explains the observed criteria put forward by Siagian in the Silalahi, namely process, implementation, organization and planning. The informants in this study used purposive sampling. The results of this study indicate that the implementation of the Fishing Vessel Feasibility Monitoring carried out by the Harbormaster Office has not been going well. Obstacles in the implementation of supervision are also one of the causes so that the supervision carried out by the Benoa Class II Port Authority is not optimal. This research is expected to be able to provide new ideas and input from the Benoa Class II Port Authorityand Port Authority Offices. Keywords: Supervision, Feasibility of Fishing Vessels